Improving cardiovascular risk stratification through multivariate time-series analysis of cardiopulmonary exercise test data - Evangelos Ntalianis; Nicholas Cauwenberghs; František Sabovčik; Everton Santana; Francois Haddad; Jomme Claes; Matthijs Michielsen; Guido Claessen; Werner Budts; Kaatje Goetschalckx; Véronique Cornelissen; Tatiana Kuznetsova (iScience, 2024)
Summary: Nowadays cardiorespiratory fitness (CRF) is assessed using summary indexes of cardiopulmonary exercise tests (CPETs). Yet, raw time-series CPET recordings may hold additional information with clinical relevance. Therefore, we investigated whether analysis of raw CPET data using dynamic time warping combined with k-medoids could identify distinct CRF phenogroups and improve cardiovascular (CV) risk stratification. CPET recordings from 1,399 participants (mean age, 56.4 years; 37.7% women) were separated into 5 groups with distinct patterns. Cluster 5 was associated with the worst CV profile with higher use of antihypertensive medication and a history of CV disease, while cluster 1 represented the most favorable CV profile. Clusters 4 (hazard ratio: 1.30; p = 0.033) and 5 (hazard ratio: 1.36; p = 0.0088) had a significantly higher risk of incident adverse events compared to clusters 1 and 2. The model evaluation in the external validation cohort revealed similar patterns. Therefore, an integrative CRF profiling might facilitate CV risk stratification and management.